2021
DOI: 10.1038/s41522-021-00237-0
|View full text |Cite
|
Sign up to set email alerts
|

The structure of Brazilian Amazonian gut microbiomes in the process of urbanisation

Abstract: Shifts in subsistence strategy among Native American people of the Amazon may be the cause of typically western diseases previously linked to modifications of gut microbial communities. Here, we used 16S ribosomal RNA sequencing to characterise the gut microbiome of 114 rural individuals, namely Xikrin, Suruí and Tupaiú, and urban individuals from Belém city, in the Brazilian Amazon. Our findings show the degree of potential urbanisation occurring in the gut microbiome of rural Amazonian communities characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Even though the children from the Adadle woreda follow a traditional agropastoral lifestyle, we observed that their fecal microbiota composition and function was significantly different than the one in children from other traditional communities. In recent years, numerous studies have highlighted the associations between bacterial taxa and specific lifestyles 14 16 , 19 , 20 , 45 , 48 50 . In accordance with these studies, we showed that the agropastoral way of living of the children from the Adadle region shapes their microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the children from the Adadle woreda follow a traditional agropastoral lifestyle, we observed that their fecal microbiota composition and function was significantly different than the one in children from other traditional communities. In recent years, numerous studies have highlighted the associations between bacterial taxa and specific lifestyles 14 16 , 19 , 20 , 45 , 48 50 . In accordance with these studies, we showed that the agropastoral way of living of the children from the Adadle region shapes their microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…The captivity conditions of wild animals (e.g., [ 72 , 73 ]) and even urbanization of human populations (e.g., Schaan et al [ 74 ]) have been shown to alter the gut microbiomes of these macroorganisms. Of the 12 fish species investigated in the present study, and according to the Hellenic Statistical Authority ( https://www.statistics.gr/en/home/ ), only Pagrus pagrus is included in the list of farmed fish in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…The captivity conditions of wild animals [e.g., [70, 71]] and even urbanization of human populations [e.g., [72]] have been shown to alter the gut microbiomes of these macroorganisms. Of the 12 fish species investigated in the present study, and according to the Hellenic Statistical Authority (https://www.statistics.gr/en/home/), only Pagrus pagrus is included in the list of farmed fish in Greece.…”
Section: Discussionmentioning
confidence: 99%